UV254 absorbance as real-time monitoring and control parameter for micropollutant removal in advanced wastewater treatment with powdered activated carbon. (1st May 2016) - Altmann, Johannes; Massa, Lukas; Sperlich, Alexander; Gnirss, Regina; Jekel, Martin
Abstract: This study investigates the applicability of UV absorbance measurements at 254 nm (UVA254 ) to serve as a simple and reliable surrogate parameter to monitor and control the removal of organic micropollutants (OMPs) in advanced wastewater treatment applying powdered activated carbon (PAC). Correlations between OMP removal and corresponding UVA254 reduction were determined in lab-scale adsorption batch tests and successfully applied to a pilot-scale PAC treatment stage to predict OMP removals in aggregate samples with good accuracy. Real-time UVA254 measurements were utilized to evaluate adapted PAC dosing strategies and proved to be effective for online monitoring of OMP removal. Furthermore, active PAC dosing control according to differential UVA254 measurements was implemented and tested. While precise removal predictions based on real-time measurements were not accurate for all OMPs, UVA254 -controlled dynamic PAC dosing was capable of achieving stable OMP removals. UVA254 can serve as an effective surrogate parameter for OMP removal in technical PAC applications. Even though the applicability as control parameter to adjust PAC dosing to water quality changes might be limited to applications with fast response between PAC adjustment and adsorptive removal (e.g. direct filtration), UVA254 measurements can also be used to monitor the adsorption efficiency in more complex PAC applications. Graphical abstract: Highlights: Micropollutant removal correlates with UVA254 decrease in PAC applications. Lab-scale correlations can predict removals in pilot-scale PAC treatment stages. Real-time UVA254 measurements are suitable for monitoring of micropollutant removal. UVA254 -controlled dynamic PAC dosing achieves stable micropollutant removals.